Dauricine Attenuates Spatial Memory Impairment and Alzheimer-Like Pathologies by Enhancing Mitochondrial Function in a Mouse Model of Alzheimer's Disease - Chen, Chongyang; Liu, Pan; Wang, Jing; Yu, Haitao; Zhang, Zaijun; Liu, Jianjun; Chen, Xiao; Zhu, Feiqi; Yang, Xifei (Frontiers in Cell and Developmental Biology, 2021)
Alzheimer’s disease (AD) is characterized by extracellular amyloid plaques composed of β-amyloid (Aβ) and intracellular neurofibrillary tangles containing hyperphosphorylated tau protein. No effective therapy is available for this disease. In this study, we investigated the potential therapeutic effects of dauricine (DAU), a benzyl tetrahydroisoquinoline alkaloid, on AD, and found that DAU administration significantly improved cognitive impairments in 3xTg-AD mice by decreasing Aβ plaques and hyperphosphorylated tau and increasing the hippocampal ATP level. Proteomic and western blot analyses revealed that DAU treatment mainly modified the expression of proteins involved in mitochondrial energy metabolism, such as Aco2, Ndufs1, Cox5a, and SDHB, and that of synapse-related proteins such as Syn1 and Syn2. Pathway analysis revealed that DAU modulated the tricarboxylic acid cycle, synaptic vesicle cycle, glycolysis, and gluconeogenesis in 3xTg-AD mice. Our study suggests that DAU may be a potential drug for the treatment of AD.